PENGARUH LEVERAGE, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS - ,Volta Diyanto, Taqwa Anshari Nasution , Enni Savitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to examine and analyze the effect of Leverage, Liquidity, andCompany Size on Profitability in Metals and Other Metals sub-sector companieslisted on the Indonesia Stock Exchange during the 2019-2021 period. This study isclassified as a quantitative research. The total population for this study is 15companies, and the number of companies that meet the criteria is 11. Thesampling technique used is purposive sampling. The analytical method used ismultiple linear regression analysis using SPSS 25 software. The results of thisstudy indicate that leverage, liquidity, and firm size have no significant effect onprofitability. This shows that there is no relationship between leverage, liquidity,and company size in achieving profitability for companies in the metals sub-sectorand other types listed on the Indonesia Stock Exchange.Keywords : Leverage, Liquidity, and Company Size, Profitability